Antisemitism and Jewish Children and Youth in Australia’s Capital Territory Schools - Ben-Moshe, Danny (2014)
Issues pertaining to religion and Australian schools have generated a significant amount of controversy and scholarly attention in recent years, and much of the attention in the religion and schools debate has focused on Muslim and non-religious children’s experiences (Erebus International, 2006; Halafoff, 2013). This article, by contrast, explores the manifestations of antisemitism as experienced by Jewish children and youth in Canberra schools. It considers the characteristics of antisemitism; when and why it occurs; its impact on the Jewish children and young people; and also the responses to it by them, the schools and the Jewish community. Based on focus groups with the Jewish students and their parents, the study reveals that antisemitism is common in Canberra schools, as almost all Jewish children and youth in this study have experienced it. The findings from this study suggest that there is a need for more anti-racism education. Specifically there is an urgent need for educational intervention about antisemitism, alongside education about religions and beliefs in general, to counter antisemitism more effectively and religious discrimination more broadly in Australian schools.